Analysis of binding residues in monoclonal antibody with high affinity for the head domain of the rat P2X4 receptor. (10th November 2020) - Igawa, Tatsuhiro; Kishikawa, Shuhei; Abe, Yoshito; Tsuda, Makoto; Inoue, Kazuhide; Ueda, Tadashi
Abstract: P2X4 receptor is known to be involved in neuropathic pain. In order to detect the expression of P2X4 receptor on microglia at the time of onset of neuropathic pain, one approach consists on the preparation of the monoclonal antibodies with both selective binding and high affinity. We have recently established a monoclonal antibody (named 12-10H) which had high affinity to rat P2X4 receptor expressed in 1321N1 cells. The dissociation constants of the complex between the monoclonal antibodies obtained so far and the head domain (HD) in the rat P2X4 receptor were in the nanomolar range. To improve the affinity by rational mutations, we need to know the precious location of the binding site in these monoclonal antibodies. Here, we have analysed and identified the binding residues in the monoclonal antibody (12-10H) with high affinity for the HD of the rat P2X4 receptor by site-directed mutagenesis. Graphical Abstract: